2013
DOI: 10.4103/0975-7406.116825
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obesity activity of chloroform-methanol extract of Premna integrifolia in mice fed with cafeteria diet

Abstract: Aim of the study:Aim of the present study was to evaluate the anti-obesity activity of chloroform:methanol extract of P. integrifolia (CMPI) in mice fed with cafeteria diet.Materials and Methods:Female Swiss Albino mice were divided into six groups, which received normal and cafeteria diet, standard drug simvastatin (10 mg/kg) and CMPI (50, 100 and 200 mg/kg) daily for 40 days. Parameters such as body weight, body mass index (BMI), Lee index of obesity (LIO), food consumption, locomotor behavior, serum glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…The findings suggest that CMPIpossesses anti-obesity activity that substantiates its ethno-medicinal use in the treatment of obesity. [ 40 ] The effect of aqueous enriched fraction of P. integrifolia root (AEFPIR) against cafeteria diet induced obesity in Swiss Albino Mice was studied. There was a significant decrease in body weight, BMI, food consumption and in the levels of serum glucose, triglyceride, total cholesterol, LDL, and VLDL with a significant increase in the level of HDL in mice treated with simvastatin and AEFPIR groups compared with cafeteria diet group.…”
Section: Anti-obesity/hypolipidemicmentioning
confidence: 99%
“…The findings suggest that CMPIpossesses anti-obesity activity that substantiates its ethno-medicinal use in the treatment of obesity. [ 40 ] The effect of aqueous enriched fraction of P. integrifolia root (AEFPIR) against cafeteria diet induced obesity in Swiss Albino Mice was studied. There was a significant decrease in body weight, BMI, food consumption and in the levels of serum glucose, triglyceride, total cholesterol, LDL, and VLDL with a significant increase in the level of HDL in mice treated with simvastatin and AEFPIR groups compared with cafeteria diet group.…”
Section: Anti-obesity/hypolipidemicmentioning
confidence: 99%
“…(Verbenaceae), commonly known as Arni or Agnimantha [1,2] have been widely used for obesity and other obesity associated disorders. [3] P. integrifolia root extract is an active ingredient of many ayurvedic preparations such as Arishtam, Avaleham, Kvatham, Ghritam and Tailum. [4] Roots are used in the treatment of diabetes, chyluria, inflammations, swellings, bronchitis, dyspepsia, liver disorders, piles, constipation and fever.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Moreover, alkaloids, carbohydrates, amino acids, steroids, flavonoids, glycosides, tannins and phenolic compounds were found in preliminary phytochemical screening of the aqueous enriched fraction of P. integrifolia root (AEFPIR, aqueous extract). [15] P. integrifolia has been reported for its potential actions such as antidiabetic, hypoglycemic and antihyperglycaemic, [16][17][18] anti-inflammatory, [7,19,20] immunomodulatory, [21] cardiac stimulant and cardioprotective, [22,23] analgesic and antibacterial, [24] antimicrobial, [25][26][27] anti-arthritic, [19,28] hepatoprotective, [29][30][31] in-vitro cytotoxic and tumor suppression, [31,32] hypolipidemic or anti-hyperlipidemic and anti-obesity, [3,[33][34][35][36] neuroprotective, [37] antiparasitic, [38] antioxidant, [14,20,29,30,32,39,40] anticoagulation, [41] antitumor, [42] gastroprotective and antiulcer [43] and longevity-promoting. [44] The herbal formulations containing P. integrifolia were also evaluated for their memory enhancing, [45] hypolipidemic, [46] and in-vitro bioactivity effects.…”
Section: Introductionmentioning
confidence: 99%
“…The high fat or cafeteria diet has been reported to induce hyperphagia in rats 36 which results in high fat stores resulting in increased body weight 37,38 . The result of our present study supports the above findings as we have observed increase in body weight and food consumption in the high fat diet fed mice but the water intake was significantly lower in HFD fed mice.…”
Section: Discussionmentioning
confidence: 99%